2008
DOI: 10.1016/j.tsf.2007.05.081
|View full text |Cite
|
Sign up to set email alerts
|

Use of surface plasmon-coupled emission for enhancing light transmission through Top-Emitting Organic Light Emitting Diodes

Abstract: In this paper, we perform surface plasmon-coupled emission studies on Rhodamine 6G molecules embedded in a corrugated structure of a thin film composed of fluorinated silica particles, and a binding medium. Our results show enhancements of photoluminescence due to surface corrugation. By varying the size of the fluorinated silica nanoparticles we were able to control the surface correlation length scale of the corrugated surface structure. It was found that the coupling efficiency of the directional light emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…And the light for SPP1 mode was scattered into the air caused by the rough surface of the TCs. [15] The schematic energy band diagram of transparent PeLED is depicted in Figure 1b. The energy level values of each layer are taken from the literature.…”
Section: Transparent Peledsmentioning
confidence: 99%
“…And the light for SPP1 mode was scattered into the air caused by the rough surface of the TCs. [15] The schematic energy band diagram of transparent PeLED is depicted in Figure 1b. The energy level values of each layer are taken from the literature.…”
Section: Transparent Peledsmentioning
confidence: 99%
“…It was reported that 80% of the emitted light from OLED devices is confined in the substrate [6,7]. Various methods have been proposed to extract the emitted light, such as waveguide modes [8,9], micro lens arras [10] and utilization of surface plasmons [11,12]. The extraction of light from the OLED devices using surface plasmons is made by incorporated in the polymer emitting layer of the gold or silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In view of explosive increase in demands for AMOLED in recent years, future prospects of OLED for general illumination and display technology seem to be very promising, and the fact that it contains no Hg and Pb, and generates no infrared and ultraviolet radiation qualifies it for environmentally and humanly friendly display technology. Whereas huge improvements in the internal quantum efficiency have been achieved by ingenious design of molecular engineering, major contribution to the extension of lifetime comes from encapsulation engineering, and still low light out-coupling efficiency awaits applications of recently discovered surface plasmon coupled emission in conjunction with metallic nanotechnology [1].…”
Section: Introductionmentioning
confidence: 99%